Hydrogel Potential of Piper Crocatum (Piper Crocatum) Red Extract to Accelerate Perineum Wound Healing and Staphylococcus Aureus Bacteria Growth in Postpartum - Shelvi Ovi Lestari; Krisdiana Wijayanti; Bedjo Santoso; Arwani Arwani; Suryati Kumorowulan (JURNAL KEBIDANAN, 2024)
The prevalence of perineal rupture increases every year, as a result, the greater the chance of puerperal infection in postpartum mothers. Factors that cause puerperal infection is the care of the perineal wound that is not paid attention to. One of the complementary treatments uses herbal plants made from red betel leaf (Piper crocatum) in the form of hydrogel preparations. Proving the potential of red betel leaf hydrogel (Piper crocatum) against accelerated perineal wound healing and staphylococcus aureus bacterial growth. This type of quantitative research uses a quasi-experimental method with purposive sampling, post-test design only with control group. Sampling was in accordance with the inclusion criteria with a sample size of 45 respondents, 15 control respondents, 15 respondents to intervention I with a dose of 2x1 a day and 15 respondents to intervention II with a dose of 3x1 a day. Data was obtained from the REEDA score assessment scale which was obtained from the assessment of Redness, Edema (Swelling), Eccymosis (Bleeding), Discharge (Extraction) and Approximation (Wound union) and vaginal swab samples carried out on days 3 and 7 for 7 days. The analysis used to assess variables is the Wilcoxon and Mann Whitney tests. The analysis used to assess the variables is the Wilcoxon and Mann Whitney test. Red betel leaf hydrogel intervention 2x1 a day and intervention 3x1 a day has the potential to accelerate perineal wound healing and decrease the growth of S. aureus bacteria with p-value 0.05, so it can be interpreted that there is a significant difference effect. The greatest decreasing value in reducing the REEDA score and the growth of S. aureus bacteria was the 3x1 a day intervention group, namely 4.60 and 8.74, so it can be concluded that the 3x1 intervention was more effective than the 2x1 a day intervention.